Hotel Reservation System - K.G.N.D, Nandasiri; M.I.S, Gamage; M.Y, Wanniarachchi; N.V.M, Lakshani; D.I De Silva; Cooray, Dulanji (International Journal of Engineering and Management Research, 2022)
The essay "Hotel Management System" focuses on managing hotel functions between the customer and the hotel. This system is divided into four components food, hall, room, and taxi. An administrator would be capable of managing taxis, menus, halls, and rooms, whereas a customer would be able to view menus and book a hall, room, or taxi. This paper discusses how the system manages all of these functionalities. In addition, the system has been designed to generate reports on every functionality for the administrator to effectively administer the system. This system includes several features, each of which is accessible to either the administrator or the customer. The main goal of this paper is to make the hotel's fundamental functions with customers easier and to provide an online presentation of the hotel for customers to connect more.